Are Routine Postoperative Radiographs Necessary During the First Year After Posterior Spinal Fusion for Idiopathic Scoliosis? A Retrospective Cohort Analysis of Implant Failure and Surgery Revision Rates. Issue 1 (January 2015) - Garg, Sumeet; Kipper, Emily; LaGreca, Jaren; Carry, Patrick; Erickson, Mark
<x xml:space="preserve">Abstract</x> Background: Radiographs are routinely obtained at postoperative visits during the first year after posterior spinal fusion (PSF) for idiopathic scoliosis (IS). The goal of this study was to determine how often radiographic findings change postoperative care. Methods: A total of 227 consecutive patients aged 10 to 21 years who underwent surgery for IS at our institution from 2004 to 2010 were identified. Charts were reviewed to determine the frequency of the following clinical symptoms during the first year after surgery: pain greater than expected, implant prominence, and sensory/motor disturbance. Radiographs were reviewed to identify implant failure and curve change. Logistic regression analysis was used to identify clinical symptoms associated with treatment deviation. Results: During the first year after surgery, an average of 6 (range, 2 to 12) radiographs were obtained from patients during an average of 3 (range, 2 to 10) follow-up visits. Pain (14%) was the most common symptom. Neurologic symptoms (13%) and implant prominence (4%) were less common. Implant failure was identified in 4 subjects (2%), of which 3 required revision surgery. The incidence of revision surgery was 2.9/1000 radiographs (95% confidence interval, 0.6-8.3). Curve progression >5 degrees in the uninstrumented curve occurred in 2 patients (0.9%). Curve progression did not result in a change in treatment for any of the patients. Pain was the only clinical symptom associated with implant failure (P=0.0047). 169/227 patients did not have any symptoms and only one of these underwent revision surgery. The sensitivity of a clinical test, which uses the presence of pain to guide the need for radiographic evaluation and rule out implant failure, was 75%, specificity 87%, positive predictive value 10%, and negative predictive value 99.5%. Conclusions: After obtaining baseline postoperative radiographs, additional radiographs during the first year after surgery for IS may not be required in the absence of clinical symptoms. Reducing the number of radiographs taken during the first year after surgery for IS in patients without symptoms can reduce radiation exposure to patients and health care costs without affecting treatment. Level of Evidence: Level II, Diagnostic Study.